Mixed martial arts unleashed [ mastering the most effective moves for victory - Dimic, Mickey; Miller, Christopher , 1977- (McGraw-Hill professional, 2009)
"Mickey Dimic is a great coach and a terrific fighter. "Mixed Martial Arts Unleashed" does an excellent job covering everything MMA beginners need to know to prepare themselves before entering the ring, in addition to providing some knockout tips and drills for advanced fighters."-Carlos Newton, UFC Welterweight World Champion Today, millions the world over are getting fit and fighting hard with mixed martial arts,